Comparison of In Vitro Assays in Selecting Radiotracers for In Vivo P-Glycoprotein PET Imaging - Renske M. Raaphorst; Heli Savolainen; Mariangela Cantore; Evita van de Steeg; Aren van Waarde; Nicola A. Colabufo; Philip H. Elsinga; Adriaan A. Lammertsma; Albert D. Windhorst; Gert Luurtsema (MDPI AG, 2017)
Positron emission tomography (PET) imaging of P-glycoprotein (P-gp) in the blood-brain barrier can be important in neurological diseases where P-gp is affected, such as Alzheimer´s disease. Radiotracers used in the imaging studies are present at very small, nanomolar, concentration, whereas in vitro assays where these tracers are characterized, are usually performed at micromolar concentration, causing often discrepant in vivo and in vitro data. We had in vivo rodent PET data of [11C]verapamil, (R)-N-[18F]fluoroethylverapamil, (R)-O-[18F]fluoroethyl-norverapamil, [18F]MC225 and [18F]MC224 and we included also two new molecules [18F]MC198 and [18F]KE64 in this study. To improve the predictive value of in vitro assays, we labeled all the tracers with tritium and performed bidirectional substrate transport assay in MDCKII-MDR1 cells at three different concentrations (0.01, 1 and 50 µM) and also inhibition assay with P-gp inhibitors. As a comparison, we used non-radioactive molecules in transport assay in Caco-2 cells at a concentration of 10 µM and in calcein-AM inhibition assay in MDCKII-MDR1 cells. All the P-gp substrates were transported dose-dependently. At the highest concentration (50 µM), P-gp was saturated in a similar way as after treatment with P-gp inhibitors. Best in vivo correlation was obtained with the bidirectional transport assay at a concentration of 0.01 µM. One micromolar concentration in a transport assay or calcein-AM assay alone is not sufficient for correct in vivo prediction of substrate P-gp PET ligands.